First Clinical Cases of OXA-48-Producing Klebsiella pneumoniae in Peru - Morales-Moreno, Adriana (2021)
Background: Carbapenemase-producing Enterobacteriaceae (CPE) represents a global public health concern and systemic infections associated with OXA-48 carbapenemase are increasingly being reported in Latin America. Here, we present the first 2 cases of systemic infections by OXA-48-Producing Klebsiella pneumoniae in Peru. A favorable clinical response was observed after targeted treatment with colistin as a backbone.